The Reception of Western Economics in the Orient - Kirby, E. Stuart (Quarterly Journal of Economics, 1952)
I. Introduction, 409. — II. Classical Economics in the Orient, 410. — III. Post-Classical Developments in the Orient, 411. — IV. Keynesian Theory in the Orient, 414. — V. Conclusion, 416.